TSUNAMI ON 26 DECEMBER 2004: SPATIAL DISTRIBUTION OF TSUNAMI HEIGHT AND THE EXTENT OF INUNDATION IN SRI LANKA - Janaka J. Wijetunge (Science of Tsunami Hazards, 2006)
This paper examines the impact of the massive tsunami of 26 December 2004 on Sri Lanka bytracing the tsunami height, the extent of inundation and the level of damage along the affectedcoastal belt. The results of an extensive field survey that was carried out in the east, south andwest coasts to record the evidence of water levels left behind by the tsunami clearly indicate non-uniform spatial distribution of inundation along the affected coastline of the country. Thetsunami inundation had been significantly greater for most parts of the east and the south-eastcoastal areas than the south, south-west and the west coasts of Sri Lanka. The results alsoindicate the possible influence of the coastal geomorphology on the extent of inundation. On theother hand, the measurements suggest maximum tsunami heights of 3 m – 7 m along the eastcoast, 3 m – 11 m on the south coast, and 1.5 m – 6 m on the west coast.